Role of autumn Arctic Sea ice in the subsequent summer precipitation variability over East Asia. (5th August 2019) - Liu, Yang; Zhu, Yali; Wang, Huijun; Gao, Yongqi; Sun, Jianqi; Wang, Tao; Ma, Jiehua; Yurova, Alla; Li, Fei
Abstract: This study explored the interannual relationship between autumn Arctic sea ice concentration (SIC) and the subsequent summer precipitation over East Asia (EASP). Since the late‐1990s, the declining SIC in the Kara–Laptev Seas has been significantly correlated with EASP as well as extremely positive anomalies in northern China and intensely negative anomalies in central‐eastern East Asia. However, there was a weak correlation between autumn SIC and EASP before the late‐1990s. Furthermore, the anomalous precipitation pattern in summer and its connection with autumn SIC variability can be explained by the seasonal persistence of continental processes (snow depth and soil moisture) into the spring. In particular, a decreasing SIC was connected with simultaneously positive and negative precipitation anomalies over northeastern China and the Siberian region, respectively, since the late‐1990s and tends to produce corresponding soil moisture anomalies over the Eurasian continent. Declining SIC also favours increased snow depth anomalies in winter over northeastern East Asia. These anomalous signals of surface processes can persist from winter into the subsequent spring, making the connection between the autumn SIC and EASP possible. The Community Earth System Model Large Ensemble simulations further verified these physical processes. More detailed mechanism for this relationship needs to be stressed in further work by numerical simulations. The results have important implications for extending the seasonal prediction validity of EASP. Moreover, before the late‐1990s, SIC‐related circulation anomalies shifted westward and northward as negative precipitation anomalies developed over west Siberia in autumn. As a result, anomalous dry soil conditions in Siberia persisted into the subsequent spring and then led to wetter‐than‐normal conditions through locally negative soil moisture–precipitation feedback before the late‐1990s. Abstract : First SVD mode of autumn SIC and subsequent summer precipitation for the period 1979/1980–2016/2017. (a) The spatial pattern of SVD1‐SIC, (b) the spatial pattern of SVD1‐precipitation and (c) the corresponding time series.